Cross-cultural aspect of linguistics as a phenomenon of modern philosophy of education - Bogdanov, Oleksandr (Skhid, 2013)
The article considers the essence and characteristics of the cross-cultural approach, the tendencies of the development of cultural studies, highlighted features of intercultural and interethnic communication